Didactic materials to teach english vocabulary to the first year preschool students at unidad educativa Carrera Sánchez Bruno, Ballenita, Santa Elena province, 2015-2016. - Peñafiel Viteri, Cielo Norma (2016)
The research paper “Didactic teaching materials to improve English vocabulary in preschool students” is divided into the theoretical and the practical part. The theoretical part provides a general aspect in teaching languages to children and their development. It also explains the basic terms and principles of teaching students and methods for children, suitable for these activities at this age. Recreational activities denote an important motivation for learning, because when the child plays, at the same time are learning or acquiring new information, experimenting, exploring and discovering their environment, and introducing them into games as teaching strategies provides them fun to stimulate the development of communicative competence. For the development of this investigation, it was important the application of different methods, such as, qualitative, quantitative, and deductive-indictive.for each method previously mentioned, different instruments were applied in order to collect information. The application of the qualitative method allowed the implementation of surveys; therefore, the principal from Unidad Educativa “Carrera Sánchez Bruno” and one English language teaching expert were interviewed providing current information about the vocabulary instruction and the importance of using didactic resources during this process. Moreover, the quantitative method allowed the application of surveys to the fourteen preschool students’ parents and English teachers; this collected information was included in this research paper by using charts and statistical graphics in order to present parents and teachers’ responses.